2008
DOI: 10.1186/1471-2474-9-52
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor alpha drugs in rheumatoid arthritis: systematic review and metaanalysis of efficacy and safety

Abstract: Background: To analyse available evidence on the efficacy and safety of anti-TNF drugs (infliximab, etanercept and adalimumab) for treating rheumatoid arthritis (RA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
141
2
11

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(160 citation statements)
references
References 60 publications
6
141
2
11
Order By: Relevance
“…The metaanalyses by Kristensen, et al and Nixon, et al concluded to equal efficacy for 3 anti-TNF-α agents: infliximab, etanercept, and adalimumab 9,11 , while that by Alonzo-Ruiz, et al determined equal efficacy for etanercept or adalimumab and MTX 10 . In contrast, 2 metaanalyses determined the superiority of anti-TNF-α agents in comparison with anakinra 11,13 .…”
Section: Discussionmentioning
confidence: 98%
“…The metaanalyses by Kristensen, et al and Nixon, et al concluded to equal efficacy for 3 anti-TNF-α agents: infliximab, etanercept, and adalimumab 9,11 , while that by Alonzo-Ruiz, et al determined equal efficacy for etanercept or adalimumab and MTX 10 . In contrast, 2 metaanalyses determined the superiority of anti-TNF-α agents in comparison with anakinra 11,13 .…”
Section: Discussionmentioning
confidence: 98%
“…Clinical trial and postmarketing surveillance data have indicated an increased risk of certain adverse events (AE) associated with biologic DMARD use: Mycobacterium tuberculosis (TB) and other opportunistic infections 8 , certain autoimmune events 9,10 , malignancies 11,12 , and infusion-site reactions 13 . Determining whether there is an increase in the risk of safety events with increasing biologic exposure is of particular clinical relevance given the chronic expression of the disease and longterm treatment required.…”
mentioning
confidence: 99%
“…This association with nonmelanoma skin cancers and anti-TNF therapy was also seen in a second larger US observational study (3). As a third example, we refer to the clustering of a rare lymphoma subtype in children with inflammatory bowel disease treated with monoclonal antibodies to TNF (4,5).…”
Section: To the Editorsmentioning
confidence: 55%